Effect of different genotypes on the fruit volatile profiles, flavonoid composition and antioxidant activities of chilli peppers. (16th April 2022) - Mi, Si; Zhang, Xiangnan; Wang, Yuhang; Zheng, Meng; Zhao, Junjie; Gong, Heyou; Wang, Xianghong
Highlights: GC-IMS was applied for the untargeted profiling of volatiles in the chilli peppers. A total of 38 flavonoid-related compounds were quantified in the chilli peppers. Significant differences were observed in the two genotypes of chilli peppers. The potential discriminating volatiles and flavonoid compounds were determined. The antioxidant activities of the chilli peppers were evaluated and compared. Abstract: The main purpose of the present study was to investigate the influence of genotypes on the volatile, flavonoid-related compounds and antioxidant capacities of chilli peppers. A set of 49 volatiles were identified in the chilli peppers using gas chromatography-ion mobility spectrometry (GC-IMS). The flavonoid-related profiles were established by the simultaneous LC-MS measurement of 38 compounds. The results of chemometrics analysis reveal that Jize and Korean chilli peppers can be distinctly separated from each other. A panel of 18 volatile and 13 flavonoid-related variables with VIP > 1 and p  < 0.05 were determined as the discriminants for Jize and Korean chilli peppers. Moreover, Korean chilli peppers showed significantly ( p  < 0.05) higher antioxidant activity than Jize chilli peppers. A clear and positive correlation was observed between the antioxidant potential and individual flavonoid compounds. The current findings could facilitate the valorization of chilli peppers as bioactive and functional ingredients at various commercial levels.